Causal Model Structure Analysis of Emotional Unrest in First Time Mothers Faced with Persistent Infant Crying 6-7 Weeks Postpartum - Miwako Okamoto, RN, CNM, PhD; Megumi Matsuoka, RN, CNM, PhD (Elsevier, 2009)
First time mothers faced with a continuously crying infant, who do not know how to stop their child from crying, are at risk of developing anxiety and other types of Emotional Unrest. Because continuous Emotional Unrest may lead to an emotional crisis, it is important for healthcare providers to understand causal factors associated with Emotional Unrest among first time mothers faced with a persistently crying infant 6-7 weeks postpartum. Methods: A cross-sectional survey was carried out on a study population of 217 first time mothers with infants aged 6-7 weeks. A self-administered questionnaire was used to measure Emotional Unrest, Neigh- borhood Social Organization, Effective Parenting Support, Understanding of Crying and the Effect of Infor- mation Available on Crying, Current Parenting Environment and Characteristics of the Mother and Child. Potential causal factors for Emotional Unrest were explored using structural equation modeling. Results: One hundred and thirty two (60.8%) of the mothers experienced persistent crying in the period 6-7 weeks after the birth of their child and 108 (49.7%) mothers experienced Emotional Unrest. Factor analysis revealed five important constructs to be causal factors of Emotional Unrest: Effective Parenting Support, Effective Assistance with Regard to Crying, Confused by Information, Neighborhood Social Organi- zation and Feelings of Fatigue and Anxiety. Structural equation modeling indicated that Effective Parenting Support, Effective Assistance with Regard to Crying, Confused by Information and Neighborhood Social Organization affect Feelings of Fatigue and Anxiety, which then leads to Emotional Unrest. Conclusion: This study demonstrated that it will be necessary in future for health-care workers to pro- vide early intervention, such as accurate information about crying as well as concrete and appropriate response measures for dealing with crying. Furthermore, in motherhood/parenting classes and the dis- charge guidance conducted at birthing centers, it will be necessary to provide guidance on what kind of effective support and local area resources are available to parents following the birth of their child. [Asian Nursing Research 2009;3(1):1-14]